DEVELOPMENT OF INTERACTIVE SIGN LANGUAGE LEARNING VIDEOS TO IMPROVE INITIAL READING SKILLS (PIONIR: JURNAL PENDIDIKAN, 2025)
The purpose of national education as stated in Law Number 20 of 2003 is to develop the potential of students to become human beings of faith, piety, and noble character, as well as capable, creative, and independent. However, in practice, students with disabilities, especially deaf people, still face obstacles in obtaining equal educational services. This research aims to develop interactive learning video media based on sign language to improve the initial reading ability of deaf students. The method used is Research and Development with the ADDIE development model consisting of five stages: Analysis, Design, Development, Implementation, and Evaluation. This product was developed in first-class Indonesian subjects with body recognition materials, and tested by media experts, materials experts, and through field trials. The validation results showed that the product was declared very feasible by material experts (97.7%) and media experts (92%), and obtained high criteria for N gain results (0.81). The t-test results showed a significant increase from the pretest score (48.33) to the posttest (90.00) with a significance of 0.002. This product has a relationship between text-image-sign language in helping deaf students understand the meaning of each word to be more concrete. Thus, it can increase the mastery of basic vocabulary that underlies the initial foundation of initial reading.Keywords: Interactive learning videos, sign language, early reading, deaf students